The legal philosophy of al-Ghazali: law, language and theology in al-Mustasfa - Moosa, Ebrahim E. I. (Department of Religious Studies, 2019)
Abu Hamid al-Ghazali is a major figure in Muslim thought and famous for his writings on theology and mysticism. Al-Ghazali’s first career was that of a jurist and he had made major contributions to the jurisprudence of the Shafii school. As time goes on his juristic contributions are increasingly being relegated to a secondary level. This thesis attempts to place one of al-Ghazali's last writings on legal theory (Usul al-figh), al-Mustafa, in perspective and evaluate its significance in the genre of Usul al-figh literature. The focus of this thesis is the interface between law, language and theology as it manifests itself in a 'close reading' of al-Mustafa and his biography as a jurist. Al-Ghazali's legal theory was very much shaped by his personal biography, intellectual, political and social contexts, which in tum were constituted by the language of theology and law. The controversies centered around the use of philosophical theology and 'foreign knowledge" in the discourse of religion. Al-Ghazali attempted to negotiate the tension-ridden ideological chasms between traditionalist and rationalist tendencies by fusing and synthesising the disparate intellectual disciplines. The battlefield for these ideological conflicts was the discipline of legal theory and law. In his role as synthesiser of disciplines, a bricoleur, al-Ghazali often ended up vacillating between binary opposites, and was caught between stability and instability, order and disorder. Despite his attempts to stabilise language by means of a metaphysics, it was the semiotic nature of language that continuously destabilised his juridical and theological discourses.